2013
DOI: 10.1002/mds.25600
|View full text |Cite
|
Sign up to set email alerts
|

Population‐specific frequencies for LRRK2 susceptibility variants in the genetic epidemiology of Parkinson's disease (GEO‐PD) consortium

Abstract: Variants within the leucine-rich repeat kinase 2 gene are recognized as the most frequent genetic cause of Parkinson’s disease. Leucine-rich repeat kinase 2 variation related to susceptibility to disease displays many features that reflect the nature of complex late-onset sporadic disorders, such as Parkinson’s disease. The Genetic Epidemiology of Parkinson’s disease consortium recently performed the largest genetic association study for variants in the leucine-rich repeat kinase 2 gene across 23 different sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 15 publications
1
33
1
1
Order By: Relevance
“…Additional variants in the Roc domain such as I1371V are found in individual PD cases but have not yet been confirmed by segregation analyses in families [8, 26]. The protective R1398H variant is associated with PD in certain populations suggesting that variation within the GTPase domain may also be beneficial [2729]. The familial Y1699C mutation, identified in German-Canadian and UK families, is the only known disease-causing variant located within the COR domain (residues 1510–1850) [4, 30].…”
Section: Gtpase Domain and Activitymentioning
confidence: 99%
“…Additional variants in the Roc domain such as I1371V are found in individual PD cases but have not yet been confirmed by segregation analyses in families [8, 26]. The protective R1398H variant is associated with PD in certain populations suggesting that variation within the GTPase domain may also be beneficial [2729]. The familial Y1699C mutation, identified in German-Canadian and UK families, is the only known disease-causing variant located within the COR domain (residues 1510–1850) [4, 30].…”
Section: Gtpase Domain and Activitymentioning
confidence: 99%
“…Among the identified LRRK2 mutations, at least seven missense mutations (N1437H, R1441C, R1441G, R1441H, Y1699C, G2019S, and I2020T) are considered to be truly pathogenic based upon segregation with disease in LRRK2 -linked families (Figure 1) [4]. In addition, many LRRK2-coding variants are associated with PD risk, including G2385R and R1628P, which confer increased risk in Asian populations, whereas a N551K-R1398H haplotype may confer a protective effective [8,9]. Genome-wide association studies have also identified common variants (or single nucleotide polymorphisms) at the LRRK2 locus that increase risk for idiopathic PD, although it is not yet clear how these SNPs that are enriched in gene regulatory regions influence LRRK2 expression in different tissues [5,10].…”
Section: Leucine-rich Repeat Kinase 2 and Parkinson’s Diseasementioning
confidence: 99%
“…It has been shown that the p.1398H variant has reduced kinase activity in comparison to the wild type p.R1398 (Tan et al 2010). Given these data, the p.R1398H (rs7133914) substitution, which occurs with a MAF of approximately 7% in Caucasians and 10% in Asians (Heckman et al, in press; Tan et al, 2010), is the most likely functional variant on the haplotype. The protective effect of p.R1398H appears strongest in Asians, where consistent odds ratios of 0.75 and 0.73 have been observed in studies by Tan et al (2010) and Ross et al (2011), with a similar odds ratio of 0.79 observed in a smaller study by Chen et al (2011).…”
Section: Introductionmentioning
confidence: 99%